The Efectiveness of @hayfa.academy Instagram Account as Arabic Learning Media in Speaking Skills - Mega Satria Nurul Falah; Awaliyah Ainun Niswah (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe: 1) the advantages of the Instagram account @hayfa.academy as a medium for learning Arabic in speaking skills; 2) the views of students who want to be proficient in Arabic, who are also followers of the Instagram account @hayfa.academy on the effectiveness of its use to improve Arabic speaking skills. This research method is descriptive qualitative. This study involved 15 students who want to be proficient in Arabic. The data sources of this study include primary data from observation, interviews, and documentation, as well as secondary data from journals, books, and internet references. The collected data were validated using triangulation techniques that include observation, interviews, and documentation. Data analysis used the Miles et al. (2014) model with stages: data reduction, data presentation, and drawing conclusions. The results of the study show that: 1) the Instagram account @hayfa.academy as a medium for learning Arabic in speaking skills has advantages as a learning medium has advantages in profile, learning methods, features and content because it presents interesting visual and audio content, combines Fusha and Ammiyah languages, and offers interactive videos and pronunciation guides; 2) The majority of students feel more confident and fluent in speaking Arabic after using the Instagram account @hayfa.academy.